Phase contrast mapping MRI measurements of global cerebral blood flow across different perfusion states – A direct comparison with 15O-H2O positron emission tomography using a hybrid PET/MR system. Issue 12 (December 2019) - Puig, Oriol; Vestergaard, Mark B; Lindberg, Ulrich; Hansen, Adam E; Ulrich, Annette; Andersen, Flemming L; Johannesen, Helle H; Rostrup, Egill; Law, Ian; Larsson, Henrik BW; Henriksen, Otto M
Phase-contrast mapping (PCM) magnetic resonance imaging (MRI) provides easy-access non-invasive quantification of global cerebral blood flow (gCBF) but its accuracy in altered perfusion states is not established. We aimed to compare paired PCM MRI and 15 O-H2 O positron emission tomography (PET) measurements of gCBF in different perfusion states in a single scanning session. Duplicate combined gCBF PCM-MRI and 15 O-H2 O PET measurements were performed in the resting condition, during hyperventilation and after acetazolamide administration (post-ACZ) using a 3T hybrid PET/MR system. A total of 62 paired gCBF measurements were acquired in 14 healthy young male volunteers. Average gCBF in resting state measured by PCM-MRI and 15 O-H2 O PET were 58.5 ± 10.7 and 38.6 ± 5.7 mL/100 g/min, respectively, during hyperventilation 33 ± 8.6 and 24.7 ± 5.8 mL/100 g/min, respectively, and post-ACZ 89.6 ± 27.1 and 57.3 ± 9.6 mL/100 g/min, respectively. On average, gCBF measured by PCM-MRI was 49% higher compared to 15 O-H2 O PET. A strong correlation between the two methods across all states was observed (R 2  = 0.72, p  < 0.001). Bland–Altman analysis suggested a perfusion dependent relative bias resulting in higher relative difference at higher CBF values. In conclusion, measurements of gCBF by PCM-MRI in healthy volunteers show a strong correlation with 15 O-H2 O PET, but are associated with a large and non-linear perfusion-dependent difference.